Industrial environmental control of polycyclic aromatic hydrocarbons in organic fuel combustion product - M. S. Ivanitskiy (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE of this study lies in the computational justification of the choice of the installation location of a multipoint sampling probe in the measuring section of the flue of boiler plants of energy enterprises and thermal power plants that have a significant negative impact of emissions on the environment, in order to increase the reliability and representativeness ofinstrumental measurements during industrial environmental control (PEC) of polluting emissions (PE).   PURPOSE. Improving the environmental safety of thermal power plants in the current conditions of the introduction of state principles of technological regulation of emissions is associated with the establishment of technological emission indicators for each source of atmospheric pollution at energy enterprises with a significant negative impact on the environment. In this regard, energy enterprises should carry out round-the-clock monitoring of PE, which requires reliable instrumental control of the content of marker substances in the combustion products of power boilers by determining a representative sampling point on the flue or chimney of an energy boiler installation.   METHODS. The paper uses methods of computer simulation of gas dynamics to determine the local fields of concentration of PE and flow velocity and assess their unevenness in the flue of an energy boiler. RESULTS. Using the example of an operating energy boiler plant of a thermal power plant, a control section of the flue was determined to ensure industrial environmental control of marker substances in the combustion products of organic fuels. The average values of the concentration of PE and the flow rate of combustion products of local fields in the calculated sections and their values on the longitudinal axis of the boiler flue are determined, and their uneven distribution is estimated.   CONCLUSION. The obtained research results can be used at energy enterprises and thermal power plants to justify the choice of a control representative measuring section for conducting a PEC, and to develop an environmental efficiency improvement program (EEIP).